Prevalence and Diversity of Gastrointestinal Parasites and Tick Species in Communal Feedlots Compared to Rural Free-Grazing Cattle in the Eastern Cape Province, South Africa - Mhlangabezi Slayi; Zuko Mpisana (Parasitologia)
Gastrointestinal parasites (GIPs) and tick infestations remain critical health challenges limiting cattle productivity in rural South Africa, particularly within communal farming systems. The Eastern Cape Province, characterized by high livestock densities and variable management practices, provides a unique context in which to examine parasitic burdens across systems. This study aimed to compare the prevalence, intensity, and diversity of GIPs and tick species in cattle raised under rural communal grazing versus communal feedlot systems in the Eastern Cape Province of South Africa. A total of 160 cattle (n = 80 per system) were randomly selected for fecal and tick examinations in community-based feedlots in Holela (Centane) and Gxwalibomvu (Tsomo), as well as from surrounding rural villages. Fecal samples were analyzed using the McMaster technique to determine fecal egg counts (FEC), while tick species were identified and counted from standardized body regions. Body condition scores (BCS) were recorded, and farmer practices related to parasite control were surveyed. Results showed significantly higher GI parasite prevalence and FEC in rural community cattle compared to feedlot cattle (p < 0.05), with Haemonchus contortus and Trichostrongylus spp. being the most prevalent. Similarly, rural cattle had significantly higher tick infestation rates, dominated by Rhipicephalus microplus and Amblyomma hebraeum. Logistic regression identified rural production system, poor body condition (BCS ≤ 2), and absence of recent deworming as significant risk factors for GI parasitism (p < 0.05). Strong negative correlations were found between BCS and both FEC (r = −0.63) and tick burden (r = −0.57). Additionally, rural farmers reported lower acaricide usage and greater reliance on traditional remedies. The study confirms that rural communal systems expose cattle to higher parasitic risks due to unmanaged grazing, limited veterinary support, and poor parasite control strategies. Communal feedlots, by contrast, offer more controlled conditions that reduce parasitic burden. Integrating strategic parasite management, farmer training, and expanded veterinary outreach is essential to improving cattle health and productivity in communal areas.